Forced advection problems for testing transport schemes. (12th January 2020) - Zerroukat, Mohamed; Allen, Thomas
Abstract: In this paper, a set of forced advection problems are proposed for testing transport schemes for atmospheric models. Unlike classical passive tracer tests, these problems contain nonlinear sources, which interact with the advected quantity and therefore are more sensitive to advection errors than passive tracer tests. These tests also provide a simple framework to mimic how transport is used within real models, where all tracers fields have physical sources. Two tests are proposed: (a) a moisture problem with phase‐change scheme which can be considered as a simplified microphysics model, and (b) an atmospheric chemical reactions test which models the main drivers of the formation and destruction of ozone in the atmosphere. These tests also provides a clean and simple framework to test issues such as dynamics–physics coupling, time‐step sensitivity and overall accuracy with simple and tractable tests. Abstract : Comparison of vapour for the microphysics test after 1 day using various schemes. (a) A control solution (WENO‐CT) using fifth‐order WENO5 with a resolution R = 1000 × 500 points and △ t = 6  s ( C F L ≃ 0 . 33 ); (b) QUICK; (c) MINMOD; (d) WENO5; (e) SL3 (cubic semi‐Lagrangian); (f) SL5 (quintic semi‐Lagrangian). Apart from the control (WENO‐CT), all the other solutions are with a resolution R = 200 × 50 points and △ t = 300  s.